Primigravida Pregnant Women Knowledge Level about Stunting - Widiastuti, Yuni Puji; Iqomh, Muhammad Khabib Burhanudin (Indonesian Journal of Global Health Research, 2023)
Stunting is a global problem that occurs in children due to chronic malnutrition and chronic infections which cause children to fail to grow. Chronic malnutrition mainly occurs in the first thousand days of a child's life, which is a critical period at the start of stunting which then has long-term impacts that can recur throughout the life cycle. The incidence of stunting is still high, especially in poor and developing countries. Low education and lack of knowledge and understanding about stunting are one of the factors that contribute to the incidence of stunting, especially in adolescent girls, women of childbearing age and pregnant women. This study aims to determine the level of knowledge of pregnant women about stunting in Kendal Regency. The research design is descriptive with a cross-sectional approach. The sample used was 56 respondents taken using purposive sampling technique. This research instrument uses a knowledge questionnaire about stunting which has been tested for validity and reliability. Statistical analysis uses descriptive statistics. The research results showed that some respondents with poor knowledge were 31 respondents (55.4%), 19 respondents had moderate knowledge (33.6%) and 6 respondents had good knowledge (10.7). It is hoped that the government, especially health workers, will provide intensive health education so as to increase pregnant women's understanding, especially about stunting, both prevention and management. For future researchers, they can conduct research on the factors that influence stunting and the influence of health education on knowledge about stunting.